Taste at first (person) sight: Visual perspective modulates brain activity implicitly associated with viewing unhealthy but not healthy foods. (1st September 2018) - Basso, Frédéric; Petit, Olivia; Le Bellu, Sophie; Lahlou, Saadi; Cancel, Aïda; Anton, Jean-Luc
Abstract: Every day, people are exposed to images of appetizing foods that can lead to high-calorie intake and contribute to overweight and obesity. Research has documented that manipulating the visual perspective from which eating is viewed helps resist temptation by altering the appraisal of unhealthy foods. However, the neural basis of this effect has not yet been examined using neuroimaging methods. Moreover, it is not known whether the benefits of this strategy can be observed when people, especially overweight, are not explicitly asked to imagine themselves eating. Last, it remains to be investigated if visual perspective could be used to promote healthy foods. The present work manipulated camera angles and tested whether visual perspective modulates activity in brain regions associated with taste and reward processing while participants watch videos featuring a hand grasping (unhealthy or healthy) foods from a plate during functional magnetic resonance imagining (fMRI). The plate was filmed from the perspective of the participant (first-person perspective; 1PP), or from a frontal view as if watching someone else eating (third-person perspective; 3PP). Our findings reveal that merely viewing unhealthy food cues from a 1PP (vs. 3PP) increases activity in brain regions that underlie representations of rewarding (appetitive) experiences (amygdala) and food intake (superior parietal gyrus). Additionally, our results show that ventral striatal activity is positively correlated with body mass index (BMI) during exposure to unhealthy foods from a 1PP (vs. 3PP). These findings suggest that unhealthy foods should be promoted through third-person (video) images to weaken the reward associated with their simulated consumption, especially amongst overweight people. It appears however that, as such, manipulating visual perspective fails to enhance the perception of healthy foods. Their promotion thus requires complementary solutions.